Digital Leadership Paradox in Primary Education: Bridging the Instructional Gap through Collaborative Teacher Networks - Edo Agustian; Enung Hasanah; Achadi Budi Santosa (Jurnal Pendidikan Terapan, 2026)
Purpose: The development of digital technology in primary education presents a paradox in instructional leadership. Although schools are increasingly providing learning technologies, the transformation of instructional practices has not yet fully occurred. This study aims to analyze how teacher learning communities construct collective digital instructional leadership through reflection, collaboration, and the distribution of agency among teachers. Methods: This study employed a qualitative approach with a case study design focusing on the Kombel Ganesha teacher learning community in Yogyakarta. The participants consisted of one head of the learning community, two community administrators, and one school supervisor, who were selected purposively. Data were collected through in-depth interviews and document analysis, and were analyzed using Braun and Clarke’s thematic analysis with the assistance of ATLAS.ti. Findings: The findings revealed five major themes: agency and instructional leadership, data-based planning and assessment, technology integration and innovation, collaboration within teacher learning communities, and quality assurance and teacher role modeling. The findings indicate that teacher learning communities function as collaborative spaces for professional reflection, shared problem-solving, and instructional improvement. Collective digital instructional leadership develops through collaboration, technology integration, and institutional support, enabling teachers to address the gap between digital learning demands and pedagogical readiness. Research Implications: Teacher learning communities can serve as strategic platforms for strengthening collective digital instructional leadership and supporting sustainable pedagogical transformation in primary education. Originality: This study proposes collective digital instructional leadership as a collaborative approach to bridging the gap between digital learning demands and pedagogical readiness through teacher learning communities.